Method and apparatus for managing scheduling a multiple cluster tool - POOL, MARK A; JEVTIC, DUSAN B; SUNKARA, RAJA S (2001)
A method and apparatus for analyzing schedules for multi-cluster tools that are used in semiconductor wafer processing and similar manufacturing applications. The method and apparatus comprise a schedule analyzer and a pass-through chamber manager. The apparatus allows the user to analyze N! possible scheduling routines (algorithms) for a given multi-cluster tool configuration and a given N-step process sequence. The invention derives a plurality of possible scheduling algorithms for a given set of input parameters and then compares the algorithms by allowing either the user or an automated process to assign each processing step within the proposed schedule a rank ordered priority. Other process or wafer movement parameters may also be given ranges such that the invention can automatically derive optimal schedules with respect to various parameter values. By comparing the results achieved with each scheduling algorithm, the method identifies the "best" schedule algorithm for a specific tool and tool parameters.